Diagnostic, Prognostic, and Therapeutic Roles of Gut Microbiota in COVID-19: A Comprehensive Systematic Review - Farsi, Yeganeh; Tahvildari, Azin; Arbabi, Mahta; Vazife, Fateme; Sechi, Leonardo A.; Shahidi Bonjar, Amir Hashem; Jamshidi, Parnian; Nasiri, Mohammad Javad; Mirsaeidi, Mehdi (Frontiers in cellular and infection microbiology, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic caused by Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2) emerged in late December 2019. Considering the important role of gut microbiota in maturation, regulation, and induction of the immune system and subsequent inflammatory processes, it seems that evaluating the composition of gut microbiota in COVID-19 patients compared with healthy individuals may have potential value as a diagnostic and/or prognostic biomarker for the disease. Also, therapeutic interventions affecting gut microbial flora may open new horizons in the treatment of COVID-19 patients and accelerating their recovery. A systematic search was conducted for relevant studies published from December 2019 to December 2021 using Pubmed/Medline, Embase, and Scopus. Articles containing the following keywords in titles or abstracts were selected: "SARS-CoV-2" or "COVID-19" or "Coronavirus Disease 19" and "gastrointestinal microbes" or "dysbiosis" or "gut microbiota" or "gut bacteria" or "gut microbes" or "gastrointestinal microbiota". Out of 1,668 studies, 22 articles fulfilled the inclusion criteria and a total of 1,255 confirmed COVID-19 patients were examined. All included studies showed a significant association between COVID-19 and gut microbiota dysbiosis. The most alteration in bacterial composition of COVID-19 patients was depletion in genera , , , , , , , and and enrichment of , , , , , , and Also, some gut microbiome alterations were associated with COVID-19 severity and poor prognosis including the increment of , , , , , , , , , , and spp. and the decrement of , , , , and the Firmicutes/Bacteroidetes ratio. Our study showed a significant change of gut microbiome composition in COVID-19 patients compared with healthy individuals. This great extent of impact has proposed the gut microbiota as a potential diagnostic, prognostic, and therapeutic strategy for COVID-19. There is much evidence about this issue, and it is expected to be increased in near future.